THE SYNTACSIC PERSON IN THE INFINITIVE SENTENCE IN THE MODERN UKRAINIAN AND POLISH LANGUAGES - Корпало, О. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The author of the article analyses the semantic two-member of the infinitive one-member sentence in which the action must be done by a particular or a generic person. The methods of expressing the syntactic person in the sentences with the explicit and implicit dative case are studied.